TRANSFORMASI PENDIDIKAN KEUANGAN SYARIAH TERHADAP LITERSI MASYARAKAT DI ERA DIGITAL - amrul (IAIN Parepare, 2025)
The advancement of digital technology has transformed various sectors of life, including education and financial services. In the context of Islamic economics, Islamic financial education plays a vital role in shaping public literacy to enable individuals to understand, select, and manage financial products based on Sharia principles. This study aims to systematically examine how the transformation of Islamic financial education—through curriculum digitalization, technology-based learning media, and online outreach—affects financial literacy in the digital era. The method used is a Systematic Literature Review (SLR) of academic articles published between 2015 and 2024, sourced from indexed databases such as Scopus, Google Scholar, and DOAJ. The findings indicate that the integration of technology into Islamic financial education positively contributes to enhancing public understanding, particularly among millennials and Gen Z, regarding the principles, instruments, and practices of Sharia finance. However, digital access disparities and limited digital literacy remain major challenges. This study recommends enhanced collaboration between educational institutions, Sharia financial authorities, and the technology sector to develop inclusive and adaptive educational models suited to contemporary changes. ABSTRACT The advancement of digital technology has transformed various sectors of life, including education and financial services. In the context of Islamic economics, Islamic financial education plays a vital role in shaping public literacy to enable individuals to understand, select, and manage financial products based on Sharia principles. This study aims to systematically examine how the transformation of Islamic financial education—through curriculum digitalization, technology-based learning media, and online outreach—affects financial literacy in the digital era. The method used is a Systematic Literature Review (SLR) of academic articles published between 2015 and 2024, sourced from indexed databases such as Scopus, Google Scholar, and DOAJ. The findings indicate that the integration of technology into Islamic financial education positively contributes to enhancing public understanding, particularly among millennials and Gen Z, regarding the principles, instruments, and practices of Sharia finance. However, digital access disparities and limited digital literacy remain major challenges. This study recommends enhanced collaboration between educational institutions, Sharia financial authorities, and the technology sector to develop inclusive and adaptive educational models suited to contemporary changes. ABSTRAK Perkembangan teknologi digital telah merevolusi berbagai sektor kehidupan, termasuk pendidikan dan layanan keuangan. Dalam konteks ekonomi Islam, pendidikan keuangan syariah memegang peranan penting dalam membentuk literasi masyarakat agar mampu memahami, memilih, dan mengelola produk-produk keuangan sesuai prinsip syariah. Artikel ini bertujuan untuk mengkaji secara sistematis bagaimana transformasi pendidikan keuangan syariah—melalui digitalisasi kurikulum, media pembelajaran berbasis teknologi, dan penyuluhan daring—mempengaruhi tingkat literasi masyarakat di era digital. Metode yang digunakan adalah studi literatur sistematis (Systematic Literature Review/SLR) terhadap artikel-artikel akademik yang dipublikasikan antara tahun 2015 hingga 2024, yang diperoleh dari basis data terindeks seperti Scopus, Google Scholar, dan DOAJ. Hasil temuan menunjukkan bahwa integrasi teknologi dalam pendidikan keuangan syariah berkontribusi positif terhadap peningkatan pemahaman masyarakat, terutama generasi milenial dan Gen Z, terhadap prinsip, instrumen, dan praktik keuangan syariah. Namun demikian, disparitas akses digital dan kompetensi literasi digital masih menjadi tantangan utama. Studi ini merekomendasikan perlunya kolaborasi antara lembaga pendidikan, otoritas keuangan syariah, dan sektor teknologi untuk mengembangkan model edukasi yang inklusif dan adaptif terhadap perubahan zaman.